Pontos de abertura no ISD para outras modalidades de linguagem (Opening points in SDI to other language modalities) - Gomes, Raquel Salcedo; Raupp, Lisiane Ribeiro (Estudos da Língua(gem), 2014)
Neste trabalho, buscamos pontos de abertura no Interacionismo Sociodiscursivo (ISD) para análise de modalidades linguísticas além do texto escrito. Identificamos sua abertura às modalidades oral e sincrética, a partir da premissa de que à linguagem estão imbricadas diversas práticas sociais. Empreendemos, conjugando ao ISD elementos da Semiótica Discursiva, uma análise de texto sincrético publicado no contexto digital da Internet, no website do Ministério da Educação. A análise aponta para a substancialidade dos elementos plásticos à discursividade nesse ambiente, verificando a possibilidade profícua de abertura do ISD a outras modalidades linguísticas. PALAVRAS-CHAVE: Interacionismo Sociodiscursivo. Modalidades de linguagem. Ação de Linguagem. Texto Sincrético Digital. Semiótica Discursiva. ABSTRACT In this paper, we seek for openings points in Sociodiscursive Interactionism (SDI) for the analysis of forms of language beyond the written text. We have identified that the SDI is open to the oral and syncretic languages, under the assumption that language embeds social practices. We have undertaken, by combining elements of the SDI and Discursive Semiotics, an analysis of a syncretic text published in the digital context of the Internet, on the website of the Brazilian Ministry of Education. Our analysis points to the relevance of plastic elements for discourse in this environment, verifying the fruitful possibility of an opening in SDI to other language modalities. KEYWORDS: Sociodiscursive Interactionism. Language Modalities. Language Action. Syncretic Digital Text. Discursive Semiotics